Ship and Offshore Structure Design in Climate Change Perspective - Maria Bitner-Gregersen, Elzbieta (SpringerBriefs in Climate Studies, 2013)
Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Climate Change Management and Policy; Quality Control, Reliability, Safety and Risk